Pengaruh Kemasan Produk Makanan Ringan Merek Oishi â€œPillowsâ€ Terhadap Keputusan Pembelian Konsumen (Studi Kasus Pada Mahasiswa Strata 1 Universitas Brawijaya) - Putra, Arie Pratama (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to identify and analyze the effect of packaging on consumer purchasing decisions at UB undergraduate students , either simultaneously or partially . This research is explanatory research thatÂ  explains the causal relationships between variables through hypothesis testing . This study used a sample of 100 respondents drawn from UB undergraduate students who ever made a purchase product . Sampling using purposive sampling , judgment sampling is also called the selection of a random sample types obtained by using certain considerations , generally adapted to the purpose or research problems . Test equipment used to test the research instrument beupa validity test , reliability test , and classical assumption . Hypothesis testing was performed using the F test and t test and dominant test . Analysis using multiple linear regression analysis . From the results of research with the steps described above result that is based on the results of multiple linear regression analysis using the F test ( simultaneous ) it can be concluded simultaneously influencing purchasing decisions , then the results of t-test analysis can be concluded that partial only variable affecting promotion purchasing decisions , while the operating variables , reusable , and labeling has no effect . Based on the results of the regression coefficient (Standardized Beta Coefficients ) , respectively , it can be seen variable promotion has dominant influence on purchasing decisions Oishi brand of snackÂ  food products " Pillows " at UB undergraduate students . Keywords: Operating, Reusable, Promotion, Labelling, Consumer Decision Making